2017
DOI: 10.3389/fphar.2017.00873
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of in Silico, in Vitro, and in Vivo Analyses to Assess Anti-cancerous Potential of a Bioactive Compound from Cyanobacterium Nostoc sp. MGL001

Abstract: Escalating incidences of cancer, especially in developed and developing countries, demand evaluation of potential unexplored natural drug resources. Here, anticancer potential of 9-Ethyliminomethyl-12-(morpholin-4-ylmethoxy)-5,8,13,16-tetraaza -hexacene-2,3-dicarboxylic acid (EMTAHDCA) isolated from fresh water cyanobacterium Nostoc sp. MGL001 was screened through in silico, in vitro, and in vivo studies. For in silico analysis, EMTAHDCA was selected as ligand and 11 cancer related proteins (Protein Data Bank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The extracts of water, dimethyl sulfoxide (DMSO), and acetone all inhibited the growth of Bacillus subtilis . Interestingly, the DMSO extract, but not the water or acetone extract, showed inhibitory effects on Klebsiella pneumoniae and Escherichia coli [ 50 ]. Levert A et al, identified three novel depsipeptides and thiosulfonamides from the French Polynesian marine cyanobacteria Lyngbya majuscula , which performed strong antimicrobial activity with the minimum inhibitory concentration of 6.7 μM [ 51 ].…”
Section: Antibacterial Actionmentioning
confidence: 99%
“…The extracts of water, dimethyl sulfoxide (DMSO), and acetone all inhibited the growth of Bacillus subtilis . Interestingly, the DMSO extract, but not the water or acetone extract, showed inhibitory effects on Klebsiella pneumoniae and Escherichia coli [ 50 ]. Levert A et al, identified three novel depsipeptides and thiosulfonamides from the French Polynesian marine cyanobacteria Lyngbya majuscula , which performed strong antimicrobial activity with the minimum inhibitory concentration of 6.7 μM [ 51 ].…”
Section: Antibacterial Actionmentioning
confidence: 99%
“…MGL001 has anticancer properties. It was found that cyanocompound EMTAHDCA induced significant cytotoxic response against Dalton's lymphoma ascites (DLA) cells with an inhibitory concentration (IC50) value of 372.4 ng/ mL in a dose and time dependent manner after 24 h of incubation 66 . Several marine cyanobacterial compounds interact with certain significant molecular targets which are involved in anticancer activity resulting in controlling the death of tumor cells, this targets to start the compounds to slow down the proliferation of cancer cells by inducing apoptotic cell death 67 .…”
Section: Anticancer Activitymentioning
confidence: 99%
“…These apoptotic cells develop complex structural alterations which allow the identification of tumor cells. During the early stages, cells become smaller in size, having dense cytoplasm with thin organelles in it 66 . Cell extracts from Cyanobium sp; CENA154, Nostoc spp; CENA64 & CENA 69, Oxynema sp; CENA135 have anticancer properties against murine colon cancer line CT-26 and lung cancer 3LL found in Brazilian cyanobacterial species 2 .…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The available data can greatly help to design the new EGFR inhibitors from the diverse secondary metabolites associated with the plant and microbial sources. Apart from the plant derived compounds, the importance of secondary metabolites of microbes is reported in anticancer therapy using in vitro and in silico experiments [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%